The Existence and Motifs of Mysticism in the Short Story Collection Hilang dalam Dekapan Semeru by RJL 5-Fajar Aditya - Herson Kadir; Zilfa Achmad Bagtayan; Fikrin Ilolu (Raja Zulkarnain Education Foundation, 2026)
Mysticism is a teaching or belief that states the existence of a supreme reality that cannot be reached by human reason and can only be obtained through direct spiritual experience. This research was conducted by describing: 1) the existence of mysticism in the short story collection Hilang dalam Emkapan Semeru by RJL5-Fajar Aditya; 2) the motif of mysticism in the short story collection Hilang dalam Emkapan Semeru by RJL5-Fajar Aditya. This research uses the study of mysticism by Niels Mulder. The type of research used is qualitative with descriptive analysis method. The data of this research are in the form of quotes, sentences, and paragraphs that describe the existence and motif of mysticism. The data source is the short story collection Hilang dalam Emkapan Semeru by RJL 5-Fajar Aditya. The research data were collected and analyzed by reading, identifying, classifying data, recording, coding using observation guide sheets involving time triangulation. The results of the study show: 1) the existence of mysticism is divided into three aspects, namely material existence (sacred media such as objects considered to have mystical powers), spiritual existence (outward and inner mystical core as the starting point and goal), and moral existence (respect for the hierarchy of norms for noble harmony); 2) the motive of mysticism as a personal desire for worldly satisfaction, is divided into positive motives (good intentions, religious such as salvation or healing), and egoistic motives (black magic, pesugihan, mystical rituals, which are contrary to divine will. Overall, the short story Lost in Semeru's Embrace by RJL 5-Fajar Aditya not only represents mystical phenomena in climbing, but also contains moral messages about courage, solidarity, and respect for nature.